Analisis Dampak Likuiditas, Leverage, Good Corporate Governance Pada Nilai Perusahaan - Silviana Kartini Rahma Lailia; Nur Moch Abdillah; Bachtiar Rahman Halik (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This research aims to test and analyze Liquidity, Leverage, and Good Corporate Governance on the Company Value of food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange. The variables used in this research are Liquidity, Leverage, and Good Corporate Governance as independent variables and Company Value as the dependent variable. This type of research is quantitative research. The number of samples used in the research was 11 manufacturing companies. The sample selection method used is non-probability, namely purposive sampling, which is a sampling technique based on certain criteria determined by the researcher. The data analysis technique used is multiple linear regression. The results of hypothesis testing in the research show that liquidity has a significant effect on company value, while Leverage does not have a significant effect on company value, and Good Corporate Governance has a significant effect on company value in consumer goods companies in the food and beverage sector listed on the Indonesia Stock Exchange.